To what extent do managers use transformational leadership practices in Yemeni governmental and financial audit organizations - Sawie, Aish Ahmed Hussein, author; Davies, Tim, advisor; Quick, Don, advisor; Gloeckner, Gene, committee member; Hall, Bruce, committee member (Colorado State University. Libraries, 2015)
The purpose of this study was to examine the managers' transformational leadership practices in Yemeni governmental and financial audit organizations. In addition, the study examined the manager-employee relationship as reflected by the comparison of managers and employees' perceptions of the managers' transformational leadership practices. Furthermore, the study attempted to determine whether or not there are differences between the technical and supportive work groups and among the five specialized divisions of the organization on managers and employees' perceptions of the managers' transformational leadership practices. A survey research design was employed to collect the data from 43 managers and their 206 employees using the Leadership Practices Inventory (LPI) survey instrument. Findings indicated that there was statistically significant difference between the scores of managers and employees on all their perceptions on the managers' five transformational leadership practices. The employees rated their managers at lower scores than the managers' scores. Findings indicated that managers and their employees scored the highest on managers' leadership practices of "Enabling Others to Act" and "Encouraging the Hear." The managers and employees scored the lowest on "Inspiring a Shared Vision" and "Challenging the Process." "Modeling the Way" score was in between the two ends. The study findings suggest that there is a gap between managers and employees on the managers' transformational leadership practices and that Yemeni government organizations should bridge the gap by providing a well-designed leadership development programs. This can provide managers with the awareness and importance of transformational leadership practices to create and promote a strong relationship between managers and employees.
Keywords: government; organization; Yemen; leadership; audit; transformational leadership